1966
DOI: 10.1063/1.1727709
|View full text |Cite
|
Sign up to set email alerts
|

Far-Infrared Spectra of Trimethylene Sulfide and Cyclobutanone

Abstract: The far-infrared spectra of trimethylene sulfide and cyclobutanone have been investigated. The positions of the trimethylene sulfide bands observed are well fitted by the potential function derived from the microwave studies of Harris et al. However, some of the band shapes cannot be explained in detail although the anomalies are probably due to Coriolis terms in the Hamiltonian. The positions of the lower frequency bands of cyclobutanone can be fit approximately by a quartic—quadratic potential with a small b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…The period of oscillation corresponds to a vibrational frequency of~35 cm À1 . Far-infrared studies have revealed a vibration of frequency~36.5 cm À1 corresponding to a ring-puckering mode in the ground state of cyclobutanone which could be a candidate for this, [31] and this mode would thus have a very similar vibrational period in the 3s state.…”
Section: Cyclobutanonementioning
confidence: 99%
“…The period of oscillation corresponds to a vibrational frequency of~35 cm À1 . Far-infrared studies have revealed a vibration of frequency~36.5 cm À1 corresponding to a ring-puckering mode in the ground state of cyclobutanone which could be a candidate for this, [31] and this mode would thus have a very similar vibrational period in the 3s state.…”
Section: Cyclobutanonementioning
confidence: 99%
“…It has been demonstrated that the cyclobutanone is floppy molecule (compare with puckered, nonplanar parent cyclobutane) [7]. Its slightly distorted chair conformation is a little bit higher in energy than the parent system [8,9]. According to Tamagawa and Hilderbrandt [10], slightly distorted cyclopentanone can either be twisted, with C 2 symmetry, or it can be bent, with C s symmetry.…”
Section: Mesomorphic Propertiesmentioning
confidence: 99%
“…Cyclobutanone (C 4 H 6 0) shows a vibrational band (ν 2←3 ) at 65 cm −1 (1.95 THz) (Borgers & Strauss (1966)). Calculated IR intensities on a B3LYP/aug-cc-pVDZ level are on the order of 13.4 km/mole.…”
Section: Vinyl Cyanide Using the Sofia Upgreat Lab Setupmentioning
confidence: 99%